Penerapan Perlindungan Anak Berbasis Masyarakat Berdasarkan UU No 35 Tahun 2014 di Kota Padang - Ramadani, Dedi; Syamsir, Syamsir (Lembaga Yasin AlSys, 2025)
Child protection is a strategic issue in social development that requires cross-sectoral involvement. Padang City is one of the regions implementing a community-based child protection system through the Perlindungan Anak Terpadu Berbasis Masyarakat (PATBM) program. However, the program’s effectiveness remains in question, as cases of violence, economic exploitation, and street children persist. This study aims to analyze the implementation of community-based child protection in Padang City in accordance with Law No. 35 of 2014, focusing on the roles of the Office of Women’s Empowerment, Child Protection, Population Control, and Family Planning (DP3AP2KB), the Social Service Office, and community participation. A descriptive qualitative method was used, with data collected through in-depth interviews, observations, and document review. The findings show that child protection efforts are carried out through socialization, victim assistance, and the strengthening of PATBM cadres. Nevertheless, implementation faces obstacles such as limited resources, weak inter-agency coordination, and low parental and community awareness of children’s rights. The study concludes that while the community-based child protection program in Padang City has been implemented, its effectiveness is not yet optimal. Strengthening stakeholder collaboration, enhancing cadre capacity, and fostering active community participation are necessary to establish a more comprehensive and sustainable child protection system.